Preparedness of School Heads, Teachers and Parents of Public Elementary Schools on the Limited Face to Face Learning Modality in Zone 2, Division of Zambales - Escobar, Rod D.; Fastidio, Joan A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The study aimed to evaluate the perspective of school heads, teachers and parents on the preparedness of public elementary schools on the limited face to face learning modality in Zone 2, Division of Zambales. The researcher employed the mixed method where in a quantitative and qualitative approaches was used in the study. Descriptive and inferential statistics was employed in the study. Based on the significant results, most of the respondents are Teacher I, female, and serve for 10-14 years in the Department of Education. Parents are self- employed, most of them are college and elementary graduate and with 3-5 children. The school head & teacher-respondents perceived as Prepared in the preparation of the public elementary schools in terms of curriculum and instruction, school environment, human resource management, and budget. Based on the experienced by parent-respondents that majority of them prepare their children to bring to school such as snacks, alcohol, facemasks, and other supplies/items that will be needed for their education in accordance with school policy. The school head and teacher-respondents perceived as Sometimes a Problem in the limited face to face for leaning modality in terms of curriculum and instruction, school environment, human resource management, and budget. Based on the experienced by the parent-respondents that for fear of the COVID 19 epidemic, majority of parents bring their children with them. Some of them prefer to walk because it is more convenient and economical for them. During a pandemic, transportation is extremely expensive, and they cannot afford to ride a tricycle. There is no significant difference on the perceived level of agreement of school head and teacher-respondents on the preparations of the public elementary schools in the limited face to face learning modality when grouped according to profile of the school heads and teachers. The proposed action plan was developed based on the findings of the study. Based on the salient findings, the researchers recommended that the school heads and teachers may develop and design curriculum and instruction integrating facts on how to combat spreading the COVID 19 viruses. Encourage parents to monitor and check their children’ safety. The curriculum planner should take into account this issue, simplify activities, and eliminate extraneous themes in order to achieve mastery. Teachers are encouraged to attend trainings and seminars related on how to handle learners who are potentially infected. The administrators may consider the medical equipment such as stretchers and wheelchairs if budget warrants. Procurement of a two-way radio for easy communication in case of emergency is suggested. The principal may hold a PTA meeting to inform parents about health protocols. Future researchers may conduct a parallel study to validate the results of this study. The proposed action plan may be implemented by the school heads to the school.